Sustainable energy public policies planning: encouraging the production and use of renewable energies - Maciel Filho, Plinio Nogueira; Alcócer, Juan Carlos Alvarado; Pinto, Olienaide Ribeiro de Oliveira; Dolibaina, Lunie Imamura de Lima (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
This work analyses the model of energy production and the use of renewable energy in Brazil with a sustainable development point of view. In this regard, it is pointed out the production of renewable energy as an alternative solution to reduce expenses costs through initial investment in the implementation of an own energy generation model towards sustainability. The diversification of the energy matrix with clean and renewable sources in substitution of the energy model based on fossil energy sources, besides being environmentally correct, has a relevant national importance. In the methodological scope it is rational to leave this writing as a theoretical study, a qualitative approach and a technical bibliographic procedure. Some results, a priori, indicate that the use of alternative sources minimizes the consumption of conventional energy sources, which generates large degradation to the environment. Many of these alternative sources are plentiful in the country. Finally, we present some public policies that the Federal Government is implementing in Higher Education Federal Institutions (IFES) for the incentive and use of renewable energies.